Making the Void Fruitful - Keane, Patrick J. (Open Book Publishers, 2022)
Shedding fresh light on the life and work of William Butler Yeats—widely acclaimed as the major English-language poet of the twentieth century—this new study by leading scholar Patrick J. Keane questions established understandings of the Irish poet’s long fascination with the occult: a fixation that repelled literary contemporaries T.S. Eliot and W.H. Auden, but which enhanced Yeats’s vision of life and death.